OPTIMALISASI PENERAPAN METODE SATU GURU DUA MURID DALAM MENINGKATKAN PEMBELAJARAN KITAB KUNING DI PONDOK PESANTREN - Ita Nurpuadah; Iwan Sopwandin (Rihlah Review: Jurnal Pendidikan Islam, 2025)
Pesantren as the oldest Islamic educational institution in Indonesia has a very noble mission, where everything that is done must ultimately lead to the formation of a generation with noble morals. This can be done in various ways, either through direct exemplary behavior exemplified by the kiai and ustadz or through understanding gained after studying the yellow book. The understanding of the yellow book should be mastered by students in a not too long time, so that they are also able to practice it immediately. So to realize this, an effort that is different from the others is needed. The type of research is qualitative with a descriptive analysis approach with data collection through participatory observation, structured interviews and documentation studies. The data analysis technique is through condensation, data presentation and drawing conclusions while the data validity test is carried out by extending observations, increasing perseverance, adequacy of references, and member checks. The results of this study indicate that the implementation of the one teacher two students method at the Gemayasih Cibungur Parungponteng Tasikmalaya Islamic Boarding School was carried out with structured planning, organization that includes determining the books to be studied, determining the mudaris and determining the students, implementing the one teacher two students method which was carried out after the dawn prayer and evaluation consisting of daily and semester evaluations. The existence of this one teacher two students method has a very significant impact on the development of reading yellow books by students and santriyah, this is evidenced by always winning the sub-district and district level competitions in the 2021-2024 period in the field of MQK (Musabaqoh Qira'atul Kutub).